Misja Jana Zawadzkiego na dwory Europy Północnej w 1633 roku a geneza polityki zagranicznej Władysława IV Wazy - Szymańska, Marta (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
The main purpose of this article is to present the role of the diplomatic mission of Jan Zawadzki to the North European courts in 1633 and the role it played in shaping and implementing the foreign policy plans of Wladyslaw IV. In relation to the literature on the subject so far, an innovative approach to the subject of this mission is to transfer the perspective of research from Zawadzki’s stay at individual courts, in favor of a comprehensive analysis of his mission. Research conducted in this way shows that the king already had a very complexed vision of his actions on the European arena at the time of taking the throne of the Polish-Lithuanian Commonwealth, as evidenced by the mission of Jan Zawadzki.